2014
DOI: 10.1021/ja504374j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Angularly Substituted Trans-Fused Hydroindanes by Convergent Coupling of Acyclic Precursors

Abstract: Angularly substituted trans-fused hydroindanes are now accessible by the direct and convergent union of trimethylsilyl (TMS)-alkynes with 4-hydroxy-1,6-enynes by a process that forges three C–C bonds, one C–H bond, and two new stereocenters. The annulation is proposed to proceed by initial formation of a Ti–alkyne complex (with a TMS-alkyne) followed by regioselective alkoxide-directed coupling with the enyne, stereoselective intramolecular cycloaddition, elimination of phenoxide, 1,3-metallotropic shift, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…This is in contrast to our earlier studies that demonstrated trans -selectivity (ds = 1:5) if this annulation reaction is quenched with methanol. 6 Selectivity for formation of the cis -fused hydroindane product was also observed in reductive transposition of the structurally related allylic alcohols 14 and 16 . Here, the cis -fused hydroindane products 26 and 27 were produced in 57 and 60% yields (ds = 5:1 and 6:1, respectively).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…This is in contrast to our earlier studies that demonstrated trans -selectivity (ds = 1:5) if this annulation reaction is quenched with methanol. 6 Selectivity for formation of the cis -fused hydroindane product was also observed in reductive transposition of the structurally related allylic alcohols 14 and 16 . Here, the cis -fused hydroindane products 26 and 27 were produced in 57 and 60% yields (ds = 5:1 and 6:1, respectively).…”
mentioning
confidence: 91%
“…The result of this elimination is the production of an allylic titanium species IV that is converted to trans -fused hydroindane products by protonation ( trans -selectivity is highest when R 1 is branched). 6 While successful, this process often delivers a mixture of hydroindane products that are contaminated with an undesired alkene isomer that likely results from protonation at the primary carbon of the allylic metal system (→ 6 ; – this isomer is often difficult to remove from the trans -fused hydroindane product). Here, we demonstrate that the penultimate organometallic intermediate generated in this alkoxide-directed metallacycle-mediated [2+2+2] annulation/elimination process (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We drew inspiration from our earlier studies that resulted in a convergent strategy for the synthesis of trans -fused and angularly substituted hydrindanes [5] and reasoned that a trans -selective decalin-forming annulation could proceed by the following tandem reaction: (1) alkyne–alkyne coupling to deliver a metallacyclopentadiene ( A ), [6] (2) stereoselective intramolecular [4+2] cycloaddition to generate B , [7] (3) elimination en route to a tertiary allylic metal species ( C ), (4) isomerization to a primary allylic organometallic ( D ), and (5) regio- and stereoselective protonation by a syn -S E ′ mechanism. [5] This final protonation process has, on occasion, been difficult to control. In the hydrindane-forming annulation, protonation is selective for the generation of the trans -fused product when “R 1 ” is branched, with varying results typically favoring the cis -isomer when this substituent is not branched.…”
mentioning
confidence: 99%
“…9 While successful, we have on occasion had difficulties optimizing reaction conditions for coupling, being limited by the concentration and quality of the commercial Grignard reagents employed in initial alkyne activation, physical properties associated with the ethereal solvent that the Grignard is in, and the relatively low concentrations that are required when employing this reagent combination (initial Ti-alkyne complex formation is typically carried out at ~ 0.1M – higher concentrations often result in heterogeneous solutions). 10 In recent studies, we have turned to the reagent combination of Ti(O i -Pr) 4 /2 n -BuLi in toluene as a suitable alternative to Ti(O i -Pr) 4 /2RMgX, and have observed success in annulative coupling processes 11 and imine–allylic alcohol coupling reactions. 10 Here, we describe our efforts to employ such reaction conditions for hydroxyl-directed alkyne–alkyne coupling and report a dramatic rate enhancement for cross-coupling with the addition of TMSCl.…”
mentioning
confidence: 99%